P.Ramlee barbershop quartets: introducing an American style of singing through Malaysian culture - Wesley Allan Johnson, (Universiti Pendidikan Sultan Idris, 2016)
P.Ramlee barbershop quartets: introducing an American style of singing through Malaysian culture by Wesley Allan Johnson,